Martensopoda gen. nov. from southern Indian mountain ranges, the first genus of huntsman spiders with a cymbial spur (Araneae: Sparassidae: Heteropodinae) - Jäger, Peter (Zootaxa, 2006)
The genus Martensopoda gen. nov. is established for two species from South India with distinct and apomorphic features in their copulatory organs. A cymbial spur in the male copulatory organs is reported the first time in the Sparassidae. The embolus’ loop — unique to Heteropodinae — is oriented transversally to the plane of the alveolus. Females exhibit spirally coiled copulatory openings similar to those of Spariolenus, but with a posterior pit at the median septum and with lateral loops of the internal duct system. Martensopoda transversa sp. nov. is described from Cardamon Hills in Kerala State (male, female), Martensopoda minuscula (Reimoser 1934) comb. nov. is known only from females and is recorded from Palni Hills, Tamil Nadu State.